Inventory Management Analysis of Engine Lubricant in Transportation Company - Muhammad Yaumal Akbar; Yuanita Handayati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The increasing demand for transportation services in Indonesia has made inventory management for critical maintenance parts, particularly engine lubricants, crucial. This study analyzes engine lubricant inventory management practices at an Indonesian transportation company, which identified recurring stockouts and unmet service levels between 2021 and 2024. The study aims to determine how inventory management analysis can optimize inventory levels, improve service levels, and reduce inventory costs. The research methodology includes ABC analysis, service level analysis, lead time measurement, safety stock calculations, and economic order quantity models. The findings indicate that these methods can improve service levels and reduce inventory costs. The optimal inventory level to increase service levels to 98% is to maintain a safety stock of 5,007 liters, with a reorder point of 16,366 liters. Furthermore, using the Economic Order Quantity (EOQ) method can reduce inventory costs by around 40%.